The Digital Future of Teacher Training in Indonesia : What’s Next? - Yarrow, Noah (World Bank, Washington, DC, 2022)
This report reflects on the Indonesia’s online teacher training ecosystem based on unique data collected from both teachers and providers during the COVID-19 period. A detailed mapping of the eight largest providers of online teacher training in Indonesia was conducted, covering 25 programs. We find that the majority of programs are short in duration and focus on digital literacy skills and remote learning. Training programs were mostly provided using online lectures, few provided individual coaching, while none provided opportunities for personalized learning. Second, we conducted a nationally representative phone survey of 435 primary and junior secondary teachers spanning 30 provinces across Indonesia (66 percent of whom are female teachers). The teacher survey was conducted between February and March 2021 and covered teachers under both the Ministry of Education, Research, and Technology (MoECRT) and the Ministry of Religious Affairs (MoRA). We find that 44 percent of teachers participated in online learning during the pandemic, and that three quarters of these teachers had never participated in online training prior to the pandemic. Many training participants reported challenges in implementing what they learned from online training. Most of the teachers who participated (88 percent) would like to continue receiving training online even after the pandemic ends. These results suggest that demand for online training is expected to persist, but more can be done to improve their quality.